1980
DOI: 10.1037/h0077699
|View full text |Cite
|
Sign up to set email alerts
|

Central control of ultrasonic vocalizations in neonatal rats: I. Brain stem motor nuclei.

Abstract: Neonatal rats produce ultrasonic vocalizations in response to cold stress. The rate and intensity of these vocalizations decrease dramatically as the pup reaches maturity. The laryngeal nerves controlling the production of ultrasounds and their nuclei of origin were investigated in 10-day-old rat pups. Unilateral and bilateral transections of the inferior laryngeal nerve reduced ultrasounds to undetectable levels. Transecting the superior laryngeal nerve either unilaterally or bilaterally reduced the sound pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
54
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 7 publications
6
54
0
Order By: Relevance
“…On the other hand, the emission of USVs is related to the inferior laryngeal nerves, and inhibited by the section of inferior laryngeal nerves [12,19]. The inferior laryngeal nerves are branched from the vagus [18,19]. From these findings, the emission of USVs might be influenced by the activity of the autonomic nerve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the emission of USVs is related to the inferior laryngeal nerves, and inhibited by the section of inferior laryngeal nerves [12,19]. The inferior laryngeal nerves are branched from the vagus [18,19]. From these findings, the emission of USVs might be influenced by the activity of the autonomic nerve.…”
Section: Discussionmentioning
confidence: 99%
“…The BAT thermogenesis can be activated by cold stress via the sympathetic nervous system [9]. On the other hand, the emission of USVs is related to the inferior laryngeal nerves, and inhibited by the section of inferior laryngeal nerves [12,19]. The inferior laryngeal nerves are branched from the vagus [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…6,8 However, it has also been reported that unilateral laryngeal denervation has no effect on the intensity, duration, or frequency of USV of adult rats. 9 These conflicting reports may be due to differences in the a͒ Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is unclear if USVs are created by a constriction at the larynx or some other location in the upper airway. While results of prior laryngeal denervation studies implicate the larynx as the site of this constriction, 6,8 direct observation of the larynx during USV production would provide more compelling evidence for the larynx as the source of USVs. Although endoscopic procedures for in vivo observation of the rat larynx have been developed, 10 these methods cannot be used to visualize laryngeal movement in the awake rat.…”
Section: Introductionmentioning
confidence: 99%
“…USV emission occurs as air passes through the constricted plate of the larynx [13]. BAT activity, which is induced by cold stress, is controlled by the autonomic nervous system [10,15], the development of which is promoted by thyroid hormones in infant rats [7]. Therefore, the increased incidences and ontogenetic changes of USVs from day 0 to day 3 might depend on the development of the laryngeal nerve in the nervous system.…”
mentioning
confidence: 99%